2018
DOI: 10.1088/1367-2630/aac3c6
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and transport of nematic colloidal swarms above photo-patterned defects and surfaces

Abstract: We investigate the dynamic assembly and swarm translocation of anisometric colloidal particles dispersed in a nematic liquid crystal and driven above a photosensitive surface. We use liquid crystalenabled electrophoresis to propel these particles via an alternating electric field perpendicular to the sample cell. By manipulating the anchoring conditions on one surface of the experimental cell, we obtain a spatially extended spiral pattern of the liquid crystal orientation that induces the dynamic assembly of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In particular, Sasaki et al [38] demonstrated that single particles and multi-particle self-assembled chains, including chains with an embedded micro-cargo, can be transported through the LC medium by combining LCEP and electrohydrodynamic convection. Another remarkable collective effect of “swarming” was demonstrated by Sagués’ group [39,40,41]. The particles in the experiments were of a pear-like shape.…”
Section: Lc-enabled Electrophoresismentioning
confidence: 83%
See 1 more Smart Citation
“…In particular, Sasaki et al [38] demonstrated that single particles and multi-particle self-assembled chains, including chains with an embedded micro-cargo, can be transported through the LC medium by combining LCEP and electrohydrodynamic convection. Another remarkable collective effect of “swarming” was demonstrated by Sagués’ group [39,40,41]. The particles in the experiments were of a pear-like shape.…”
Section: Lc-enabled Electrophoresismentioning
confidence: 83%
“…The particles driven by LCEP to the center region assemble into a rotating vortex (Figure 5e,f). Even more intriguing, the aster and spiral clusters of colloids can be moved anywhere in the plane of the LC cell, by changing the location of the UV spot (Figure 5g [39,41]). All these properties allow one to design and address dynamically reconfigurable 2D lattices of clusters [39].…”
Section: Lc-enabled Electrophoresismentioning
confidence: 99%
“…Surface interactions on colloidal particles’ surface allow for the activation of their translational or rotational motion due to facile response to light or other external stimuli. , Among the key features allowing the transformation of passive colloidal inclusions into micromotors and micromachines are functionalization of azobenzene dye molecules on the surface of colloidal particles , or using azobenzene dyes in the anisotropic nematic fluid host. , , …”
Section: Liquid Crystal Colloids Fabrication Methodsmentioning
confidence: 99%
“…It will also be interesting to quantify the effect of fluid visco-elasticity [174], composition (e.g. liquid crystals [175,176]), and wall elasticity [177,178,179,180,181,182,183,184,185,186] on the collective motion of driven colloidal suspensions.…”
Section: Perspectivesmentioning
confidence: 99%